THE EFFECT OF THEMATIC LEARNING APPROACH (WEBBED MODEL AND INTEGRATED MODEL) AND SELFCONCEPT ON THE ABILITY OF READING COMPREHENTION IN GRADE 4TH ELEMENTARY SCHOOL (International Conference on Elementary Education, 2018)
This study aims to determine the effect of the theme approach (integrated model and webbed model) and self-concept of comprehension reading skills in elementary schools. This research was conducted on 4th grade students of SDN Kembangan Utara 04 Pagi, Kembangan, Jakarta Barat in 2018 with 60 elementary school students. Data retrieval was obtained through a two-track variant analysis test with treatmeant by level 2 x 2 design. Data collection techniques were used in this study with multiple choice / multiple choice tests. The results of the study showed that: (1) the reading ability of the group understanding of students using the integrated thematic model approach was higher than the group of students who studied using the themed webbed model approach. (2) the results of reading comprehension abilities do not have an interaction effect between thematic approaches and self-concepts. (3) the results of reading the understanding of groups of students who have high self-concept and learning with an integrated thematic approach to the model are no higher than the group of students who have a high self-concept who learns thematic approach to the webbed model. (4) the results of reading the understanding of groups of students who have low self-concept and learning with an integrated thematic approach to the model is not higher than the group of students who have a low self-concept who learns thematic approach to the webbed model.